Better correction of metabolic acidosis, blood pressure control, and phagocytosis with bicarbonate compared to lactate solution in acute peritoneal dialysis - Thongboonkerd V. (2014)
Lactate solution has been the standard dialysate fluid for a long time. However, it tends to convert back into lactic acid in poor tissue-perfusion states. The aim of this study was to evaluate the efficacy of magnesium (Mg)- and calcium (Ca)-free bicarbonate solution compared with lactate solution in acute peritoneal dialysis (PD). Renal failure patients who were indicated for dialysis and needed acute PD were classified as shock and nonshock groups, and then were randomized to receive either bicarbonate or lactate solution. Twenty patients were enrolled in this study (5 in each subgroup). In the shock group, there were more rapid improvements and significantly higher levels of blood pH (7.40 ± 0.04 versus 7.28 ± 0.05, p < 0.05), serum bicarbonate (23.30 ± 1.46 versus 18.37 ± 1.25 mmol/L, p < 0.05), systolic pressure (106.80 ± 3.68 versus 97.44 ± 3.94 mm Hg, p < 0.05), mean arterial pressure (80.72 ± 2.01 versus 73.28 ± 2.41 mm Hg, p < 0.05), percentages of phagocytosis of circulating leukocytes (65.85% ± 2.22 versus 52.12% ± 2.71, p < 0.05), and percentages of positive nitroblue tetrazolium (NBT) reduction test without and with stimulation (14.43 ± 1.93 versus 9.43 ± 2.12, p < 0.05 and 65.08 ± 6.80 versus 50.23 ± 4.21, p < 0.05, respectively) in the bicarbonate subgroup compared with the lactate subgroup. In the nonshock group, blood pH, serum bicarbonate, and phagocytosis assays in both subgroups were comparable. Lactic acidosis was more rapidly recovered and was significantly lower with bicarbonate solution for both shock and nonshock groups (3.63 ± 0.37 versus 5.21 ± 0.30 mmol/L, p < 0.05 and 2.92 ± 0.40 versus 3.44 ± 0.34 mmol/L, p < 0.05, respectively). Peritoneal urea and creatinine clearances in both subgroups were comparable for both shock and nonshock groups. There was no peritonitis observed during the study. Serum Mg and Ca levels in the bicarbonate subgroup were significantly lower, but no clinical and electrocardiographic abnormality were observed. We concluded that Mg- and Ca-free bicarbonate solution could be safely used and had better outcomes in correction of metabolic acidosis, blood pressure control, and nonspecific systemic host defense with comparable efficacy when compared to lactate solution. It should be the dialysate of choice for acute PD especially in the poor tissue-perfusion states such as shock, lactic acidosis, and multiple organ failure.